(3SHhfL HhH fLe cQI GdbOe(B!s - (3djheGf, OjajOs ((3HjQhJs (3gGTjJ CfWhGf CWaGds, 2022)
(3bQQ SHhfL HhH hHSjW GdGfVeGe Edi aQjb cQI bOe (B"(3ebQeTGJ SdWY(B"! (3hdcf(B... (3gd jJeJY GdUOjbGf HGdegGQGJ GddGReI? hgd CfJ eSJYO dNhV eHGQGI cQI bOe hOjI eY SHhfL HhH hCUObGFg?s
(3GdbUU GdeJQLeIs
Keywords: (3GdCOH GdEfLdjRjs; (3GdeJQLeGJs